The Ras/ERK signaling pathway couples antimicrobial peptides to mediate resistance to dengue virus in Aedes mosquitoes. - Wen-Quan Liu; Si-Qi Chen; Hao-Qiang Bai; Qi-Mei Wei; Sheng-Nan Zhang; Chen Chen; Yi-Han Zhu; Tang-Wei Yi; Xiao-Pu Guo; Si-Yuan Chen; Meng-Jie Yin; Chen-Feng Sun; et al. (Public Library of Science (PLoS), 2020)
Aedes mosquitoes can transmit dengue and several other severe vector-borne viral diseases, thereby influencing millions of people worldwide. Insects primarily control and clear the viral infections via their innate immune systems. Mitogen-Activated Protein Kinases (MAPKs) and antimicrobial peptides (AMPs) are both evolutionarily conserved components of the innate immune systems. In this study, we investigated the role of MAPKs in Aedes mosquitoes following DENV infection by using genetic and pharmacological approaches. We demonstrated that knockdown of ERK, but not of JNK or p38, significantly enhances the viral replication in Aedes mosquito cells. The Ras/ERK signaling is activated in both the cells and midguts of Aedes mosquitoes following DENV infection, and thus plays a role in restricting the viral infection, as both genetic and pharmacological activation of the Ras/ERK pathway significantly decreases the viral titers. In contrast, inhibition of the Ras/ERK pathway enhances DENV infection. In addition, we identified a signaling crosstalk between the Ras/ERK pathway and DENV-induced AMPs in which defensin C participates in restricting DENV infection in Aedes mosquitoes. Our results reveal that the Ras/ERK signaling pathway couples AMPs to mediate the resistance of Aedes mosquitoes to DENV infection, which provides a new insight into understanding the crosstalk between MAPKs and AMPs in the innate immunity of mosquito vectors during the viral infection.